BMI, Weight Discrimination, and the Trajectory of Distress and Well‐Being Across the Coronavirus Pandemic. Issue 1 (29th November 2020) - Sutin, Angelina R.; Stephan, Yannick; Luchetti, Martina; Aschwanden, Damaris; Strickhouser, Jason E.; Lee, Ji Hyun; Sesker, Amanda A.; Terracciano, Antonio
Abstract : Objective: The purpose of this study was to examine the trajectory of psychological distress and well‐being across the coronavirus pandemic by BMI category and weight discrimination. Methods: Participants ( N = 1, 590) were assessed three times: early February 2020 before the coronavirus crisis in the United States and again in mid‐March and late April 2020. Participants reported their weight, height, and weight discrimination in February. Depressed affect, loneliness, purpose in life, life satisfaction, and perceived support were assessed in all surveys; anxiety and stress were assessed in the March/April surveys. Results: Prior to the pandemic, reporting weight discrimination or being in the underweight or obesity 2 to 3 categories was associated with more distress and lower well‐being. Weight discrimination, not BMI, was associated with a twofold increased risk of incident depression from before to during the pandemic. Weight discrimination was associated with declines in purpose in life and life satisfaction across the pandemic. BMI categories were unrelated to changes in distress/well‐being across the pandemic. Conclusions: Prior to the pandemic, BMI and weight discrimination were vulnerabilities for greater distress and lower well‐being. Weight discrimination, but not BMI, increased risk for incident depression and declines in well‐being during the coronavirus pandemic.